Discovering nature globalization and environmental culture in China and Taiwan - Weller, Robert P. (Cambridge Univ. Press, 2006)
Robert P. Weller's richly documented account describes the extraordinary transformations which have taken place in Chinese and Taiwanese responses to the environment across the twentieth century. Indeed, both places can be said to have 'discovered' a new concept of nature. The book focuses on nature tourism, anti-pollution movements, and policy implementation to show how the global spread of western ideas about nature has interacted with Chinese traditions. Inevitably differences of understanding across groups have caused problems in administering environmental reforms. They will have to be resolved if the dynamic transformations of the 1980s are to be maintained in the twenty-first century. In spite of a century of independent political development, a comparison between China and Taiwan reveals surprising similarities, showing how globalization and shared cultural traditions have outweighed political differences in shaping their environments. The book will appeal to a broad readership from scholars of Asia, to environmentalists, and anthropologists.
Keywords: Culture et mondialisation - Chine; Culture et mondialisation - Taiwan; Environnement - Politique gouvernementale - Chine; Environnement - Politique gouvernementale - Taiwan; Environnement - Protection - Chine; Environnement - Protection - Taiwan; Umweltpolitik; Umweltschutz; Culture and globalization -- China; Culture and globalization -- Taiwan; Environmental policy -- China; Environmental policy -- Taiwan; Environmental protection -- China; Environmental protection -- Taiwan; Internationalisierung; Taiwan; China